Update on Novel Therapies for Pancreatic Neuroendocrine Tumors: 2013 - Dimou, Anastasios; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
<!--[if gte mso 9]> <![endif]--> Neuroendocrine tumors of the pancreas (pNETs) are classified on the basis of their differentiation as well as the functional status. Current treatment options for non resectable disease include everolimus, sunitinib, somatostatin analogs and chemotherapy. A number of trials with novel compounds and drug combinations were reported at the recent ASCO Annual Meeting. Pasireotide is a novel somatostatin analog with broader affinity for the somatostatin receptors compared to the traditional octreotide and lantreotide and it appears to be safe in patients with pNETs according to a phase I study (Abstract #e15126). The combination of octreotide with everolimus showed promising response rate and progression free survival in a phase II study (Abstract #4136). In another phase II study, the AKT inhibitor MK-2206 was well tolerated with moderate efficacy (Abstract #e15133). Last but not least, we discuss the updated data from a phase II study that used the combination of temsirolimus with bevacizumab in patients with advanced pNETs (Abstract #4032). Image: Albert Einstein Medical Center. Philadelphia, PA, USA. <!--[endif] -->